Heterogenization of polyoxometalates as solid catalysts in aerobic oxidation of glycerol. Issue 11 (21st May 2020) - Tao, Meilin; Li, Yue; Li, Yiming; Zhang, Xueyan; Geletii, Yurii V.; Wang, Xiaohong; Hill, Craig L.
Abstract : A series of heterogeneous catalysts L n PMo12 O40 (L = Al 3+, Fe 3+, Cr 3+, Ti 4+, Zr 4+, Zn 2+ ) and H x PMo11 LO39 (L = Zn 2+, Cr 3+, Fe 3+, Al 3+, Ti 4+ ) were prepared using a simple calcination treatment and were evaluated in aerobic oxidation of glycerol. Abstract : A series of heterogeneous catalysts based on phosphomolybdic salts with different metals in counter or substituent positions, L n PMo12 O40 (L = Al 3+, Fe 3+, Cr 3+, Ti 4+, Zr 4+ and Zn 2+, abbreviated as LPMo12 ) and H x PMo11 LO39 (L = Zn 2+, Cr 3+, Fe 3+, Al 3+, Ti 4+, for Ti 4+ ; the amount of O is 40, abbreviated as HPMo11 L), were prepared using a simple calcination treatment and were evaluated in aerobic oxidation of glycerol. After calcination at about 250 °C for 4 h, homogeneous L n PMo12 O40 · n H2 O and H x PMo11 LO39 · m H2 O became heterogeneous. Their specific surface areas were also enhanced as well as their activity and reusability. Similar to the homogeneous catalysts, AlPMo12 treated at 400 °C (AlPMo12 -400) was found to be the most active catalyst in glycerol oxidation to lactic acid, with 96.1% yield and 98.6% conversion at 60 °C for 5 h with 1 MPa of O2 ; it gave a turnover number (TON; TON = [LA]/[catalyst]) of 2.4 × 10 2, higher than that of AlPMo12 -250 treated at 250 °C (TON = 2.0 × 10 2 ). AlPMo12 behaved as a heterogeneous catalyst in glycerol oxidation and could be reused at least 12 times. AlPMo12 -400 also performed well in crude glycerol oxidation, affording lactic acid yields as high as 86.8%.